KONSEP PENERAPAN MOTIVASI DALAM BELAJAR - Nazila Syifa Thohiroh; Neviyarni Neviyarni; Herman Nirwana (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Motivation is a central element in learning that functions as a driver and determinant of sustained academic behavior. This study employs a systematic literature review method to analyze the concepts of intrinsic and extrinsic motivation, compiling them from the theoretical perspectives of Behaviorism, Cognitivism (ARCS Model), and Humanism (Maslow's Hierarchy of Needs). The synthesis results show that effective motivation application requires an integration of strategies: positive reinforcement (Behaviorism), clear goal setting (Cognitivism), and creating a positive classroom climate (Humanism). To address learning barriers, a Diagnosis of Learning Difficulties (DKB) followed by individualized Remedial Teaching is necessary. Motivational success relies on the teacher's expertise in integrating these theories to foster self-regulated learning.